Analisis Pembiayaan pada Koperasi Syariah XYZ Gresik - Sayyidah Diana; Wasti Reviandani (MES Management Journal, 2024)
This study aims to analyze financing at XYZ Syariah Cooperative Gresik, considering the high level of problematic financing reaching 22.77%. This topic is significant as effective financing is key to the sustainability of Islamic cooperatives in enhancing the welfare of their members. The research method used is qualitative descriptive, with data collection through interviews, observation, and document analysis. The study findings indicate that the causes of problematic financing stem from internal factors, such as non-compliance with standard operating procedures (SOP), as well as external factors, including the deteriorating economic conditions of members. The cooperative's efforts to address these issues include personal approaches, warning letters, and financing restructuring. The study concludes that strengthening creditworthiness analysis and stricter implementation of SOP are necessary to reduce the risk of problematic financing, thereby maintaining the financial stability of the cooperative. The findings of this study are expected to contribute to the development of risk management in Islamic cooperatives.